The Prophet and Poetry: Theoretical Problems of Islamic Prophetic Texts - Warits, Moh. Shalahuddin A.; Sangidu, Sangidu; Rokhman, Muh. Arif (Religió Jurnal Studi Agama-agama, 2023)
In a semiotic framework, hadith literature can be read as a prophetic text. With this perspective, hadith literature is no longer functional solely in the structure of Islamic legal sources, but more broadly as a language and discourse for the prophetic teachings of the Prophet Muhammad, which in its nature is intended “for all creatures” (li-l-‘ālamīn). This research then tries to reveal how Islamic prophetic language unit is formed in a whole prophetic text discourse. To take Halliday’s approach, a language unit can create its own language environment. Thus, hadith literature, as a medium for the functioning of a particular language unit, can create its own language environment, which is the prophetic language environment. A prophetic language, of course, will only be meaningful in its own ecosocial environment and can also become what is called “antilanguage” for different contexts. Yet, in fact, some hadith literatures show the presence of poetic texts in them. These poetic texts take the form of classical Arabic poetry from the pre-Islamic tradition which, if we refer to Quran 36:69, would be considered incompatible with prophethood. By unraveling the intertwining of these texts, this study seeks to show how the situation of intertextuality can pave the way for a new reading of Islamic prophetic texts. Poetic texts, in this case, may constitute a functional element that makes an important contribution in establishing Islamic prophetic discourse.